Use of Social Web and Perceptions of Professional Behaviours Regarding Social Web Postings among Physiotherapy Students (Indian Journal of Forensic Medicine & Toxicology, 2020)
BACKGROUND: Social media websites which facilitate exchange of user-generated content has enormouspotential in health care which allows Physiotherapists to post educational information for patients alsoto share ideas as it acts as a great source of information for research and learning. OBJECTIVE: Tosurvey students enrolled in professional physical therapy programs regarding their use of social web andperceptions of professional behaviors regarding social web postings. MATERIALS AND METHODS:A non-experimental observational type of study has been done with 100 Physiotherapy students of threedifferent years and were selected according to the selection criteria. The survey instrument was provided toparticipate in the study addressing students use of social web. RESULTS AND CONCLUSONS Studentsare unaware about the social media policy and its importance. Students should learn about the privacyconcern and professional boundaries. There is a need for social media policies and education regarding theproper use of social media